A Taxonomy and Survey of IoT Cloud Applications - T. Pflanzner; A. Kertesz (EAI Endorsed Transactions on Internet of Things, 2017)
Internet of Things (IoT) systems are realized by dynamic global network infrastructure with self-configuring capabilities, in which things can interact and communicate in the environment through the Internet by exchanging sensor data, and react autonomously to events generally without direct human intervention. Such systems can be utilized in many application areas, thus they may have very dierent properties. There is a growing number of cloud providers oering IoT-specific services, since cloud computing has the potential to satisfy IoT needs such as standardizing the custom data structures of the devices, processing and visualization tasks. IoT application developers do not only have to decide which cloud provider to use, but they also have to choose which combination of protocols and data structures best fits their application. As a result, it is necessary to know what properties these systems have and to learn to what extent cloud providers support IoT capabilities. In this paper, we address these issues and investigate 23 IoT cloud use cases and perform a detailed classification of them in a survey, and introduce a taxonomy of IoT application properties based on this survey. We also compare current cloud providers supporting IoT capabilities and gather requirements for IoT device simulation to support further research on IoT application development.